Neoliberalismo Crisis Actual - Peck, Jamie (Documentos y Aportes en Administración Pública y Gestión Estatal, 2012)
The article discuss the characteristic of the current neoliberalism to understand it as a changeable and complex project whose economic and political sustainability is continuously reinvented and whose governance and spatiality is in need of being understood differently, if a viable alternative is to be constructed. Taking the recent neoliberal crisis as a point of departure, it discusses three main and interrelated aspects: firstly, the polymorphic characteristics of neoliberalism as a process in transformation; secondly, the way in which it could be acted against this neoliberal process by bringing some contributions from Polanyi back into the analysis so as to understand neoliberalism's dynamics; thirdly, the characteristics of some current policies taking place under neoliberal process, some of which could became viable alternatives in the long term. (English)
Keywords: 21st century; POLANYI, Karl, 1886-1964; crisis; economic history; global financial crisis, 2008-2009; neoliberalism; neoliberalismo; political philosophy; political practices; practical politics; prácticas políticas; world politics - economic aspects